Identifying SME mortality factors in the life cycle stages: An empirical approach of relevant factors for small business owner-managers in Brazil - Edmundo Escriv\~ao Filho; Alexandre Farias Albuquerque; Marcelo Seido Nagano; Luiz Adalberto Philippsen; Jair de Oliveira (Journal of Global Entrepreneurship Research, 2017)
Although small and medium-sized enterprises (SME) are an important part of worldwide economy, frequently, researches on SME mortality factors ignores their characteristics. This paper discusses the relation between the SME mortality factors and the small business owner-manager, based on the life cycle stage as an essential part for a better understanding of their closure moment. The research paper was designed in two main complementary phases: (i.) a systematic review focused on failure subject, in order to capture the state of the art of the theme added by the conceptual background of classical SME studies and (ii.) a multiple case study of seven Brazilian SME with a qualitative, descriptive and empirical approach. The results show that small business owner-managers failure business did not use correctly or gave required attention to the mortality factors such as full time dedication, exercising operational activities and managerial roles, discipline, purchase abilities, negotiation, finance and family motivation in keeping up the business. The main contribution for entrepreneurship studies is the indication of an existing relation between mortality factors and the life cycle stages of SME, which evidences the changing importance of the mortality factors throughout the life cycle stages, including closure. The practical results of this paper offers new insights into the relevant SME mortality factors, opening a number of potential avenues for future studies focused on SME, mortality factors and the small business owner-manager.
Keywords: 650; Small and medium-sized enterprises; Mortality factors; Small business owner-manager; Life cycle stages